EVALUATION OF THE EFFECTIVENESS OF GREEN BELT MANGROVE IN MITIGATION OF ABRASION IN KABONGA BESAR VILLAGE, DONGGALA USING DRONE IMAGERY - Juan Imanuel; Setiyawan; Fatimah Maulida (RADJA PUBLIKA, 2026)
Abrasion beach is one of the coastal area problems that can influence changes in coastal areas and lowering quality ecosystem coast . Mangroves have function important as green belt natural that plays a role in dampen energy waves , holding back sediment , and helps guard coastal area stability . Research This aim analyze role mangrove cover and density in mitigation abrasion beach in Kabonga Besar Village , Regency Donggala . Research use approach descriptive-quantitative based drone imagery and systems Information Geographic Information System (GIS). Research results show that wide mangrove cover reaches 1.1 hectares and is still form belt green natural in the area coastal areas . The mangrove density level is classified as Good with an average of 2,233 individuals /ha. Changes in the highest tide limit show three point experience accretion with EPR values are 1.62 m/ year , 0.29 m/ year , and 1.04 m/ year , while One point experience abrasion of -0.72 m/ year . Condition the indicates that the coastal area of Kabonga Besar Village tends to relatively stable , although potential abrasion Still found at the location certain . In particular Overall , mangrove cover and density contribute in support coastal area stability as well as help reduce potential abrasion .